Physician’s Burnout: Is It A Serious Problem? (Journal of Pakistan Orthopaedic Association, 2019)
“I feel mentally and physically exhausted”, “I wish I could get rid of my patients”, “I don’t feel empathy toward my patients any more”, “whats the use of all this hard work that I am doing”. Has any of these thoughts occurred to you? If yes, you might be suffering from “Physician’s Burnout syndrome”. According to Christina Maslach, who developed the tool for measuring burnout “The Maslach Burnout Inventory (MBI), Burnout is “an erosion of the soul caused by a deterioration of one’s values, dignity, spirit and will”. A physician’s job is considered to be very stressful. However, there is a difference between “Stress” and “Burnout”. We all feel exhausted, tired and toasted after long operating hours or forty-eight hours on call. But we recharge when we go home, have good sleep, spent quality time with the family and next morning we are ready to start over with full energies. Burnout begins when we fail to recharge ourselves during the off times. That’s when we start hating ourselves and our job when we go for it the next morning.          There is a growing epidemic of physician’s burnout throughout the world. Different studies have shown that one out of three physicians’ in United States suffer from this problem. If we look around, we will find many colleagues around us suffering from this problem. Physician’s burnout is directly linked to a number of undesirable consequences. These include lower patient satisfaction, increased chances of medical error, reduced work output, increased chances of substance abuse, and in worst scenario, physician’s suicide. In short, physician’s burnout is bad for physician himself, his family, patients and his institution.